Knowledge and behaviour management in the multi-ethnic classroom: an ethnographic study of teachers' classroom-management strategies and minority pupils' participation in different school subjects. Issue 1 (2nd January 2020) - Steffensen, Tom; Havgaard, Merete Hull
ABSTRACT: Within the tradition of ethnographic classroom research, this paper studies how pupils with a minority background are disciplined and participate in different school subjects such as Danish, English, math and science in Danish primary and lower secondary school settings. Whereas most research on minority children in classroom contexts focuses either on classroom social norms or effectiveness of teaching methods, this paper aims to understand how classroom behavioural norms and the norms for legitimate participation in the knowledge practices of different subjects impact each other. On one hand, our principal findings indicate that the teacher's foregrounding of behavioural norms in the classroom seems to displace knowledge practices, producing power struggles between pupils and their teachers. On the other hand, the teacher's foregrounding of knowledge practices tends to make schooling more meaningful for pupils, thereby reducing power struggles.